ARI updates 2017 / Accounting Research Institute (Accounting Research Institute (ARI), 2017)
The Accounting Research Institute of Universiti Teknologi MARA, or ARI as it is popularly known, has had an illustrious history despite its relative youth. With its humble beginnings in 2002 as part of it Special interest Group Initiative, the institute went on, in 2009, to become just one of six centres of excellence in the country to be awarded the status of a Higher Institution Centre of Excellence, or HiCoE by the Malaysian government.